Characteristics and Outcomes of COVID-19 in Pediatric Patients with Chronic Diseases Attending Qena University Hospital, Upper Egypt - Shymaa G. Rizk; Ahmed El-Abd Ahmed; Mohammed H. Hassan; Nagwan I. Rashwan (SVU - International Journal of Medical Sciences, 2024)
Background: Considering the global SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) outbreak, comorbid conditions in children may enhance the risk of COVID-19-related severe morbidity and mortality with failure of chronic disease management. Objectives: To explore the various clinical, laboratory, and radiological presentations of COVID-19 among pediatric patients having chronic diseases and correlate the data with the outcomes of the included patients. Patients and Methods: This study was a descriptive study that was carried out on 36 pediatric patients with COVID-19 who have chronic diseases (16 cardiac patients, 8 neurological patients, 6 renal patients, 4 patients with genetic disorders, and 2 rheumatological patients) attending Pediatrics Department at Qena University Hospital. Clinical, laboratory, and radiological assessments of the included patients were performed. Serum angiotensin converting enzyme-2 (ACE-2) and tumor necrosis factor-alpha (TNF-α) were measured using commercially available ELISA kits. Results: Our study was conducted on 36 children, 22.22% of the studied cases were confirmed to have COVID-19, and 77.78% of cases were suspected. Regarding disease severity, 11.11% of cases were critical, 16.67% were severe, 44.44% were moderate and 27.78% were mild. The main symptoms were fever in 88.89%, dyspnea in 72.22%, and dry cough in 61.11%. The lymphocytic count was normal, decreased, and increased in 44.4%, 33.3%, and 22.2% of cases respectively. The neutrophilic count was increased, normal, and decreased in 55.56%, 27.7%, and 16.6% of cases respectively. TNF-alpha levels were higher in rheumatologic and neurologic groups. CT findings of COVID-19 were detected in 44.44% of cases. Regarding the outcome; 77.8% recovered, 11.11% had complications, and 5.6% died. Conclusion: Although the clinical pattern of COVID-19 among pediatric patients with chronic diseases is more or less similar to adult pattern, laboratory and imaging findings differ, so this may be helpful for early detection of COVID-19 in pediatric patients with chronic disease to avoid unwanted outcomes.